A STUDY ON THE COORDINATION BETWEEN THE SIZE OF UNDERGRADUATE EDUCATION AND REGIONAL ECONOMY IN MAINLAND CHINA'S PROVINCES: ANALYSIS AND PATHWAY RECOMMENDATIONS BASED ON 2018 DATA - YANG, Yu (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This study aims to explore the coordination between the scale of undergraduate education and regional economic development in 31 provinces in mainland China. By analysing the relevant data in 2018, the study finds that there is a strong correlation between the scale of undergraduate education and gross domestic product (GDP), but at the same time, there is an imbalance, and the scale of undergraduate education in some provinces is not coordinated with the regional economic development. This imbalance is caused by various factors such as history and culture. The study suggests specific paths for different regions to achieve the coordinated development of undergraduate education scale and regional economy.
Keywords: undergraduate education scale; regional economy; coordination; coordinated development; empirical research